On the conceptual assessment of an extensive retrofit of a regional aircraft on the example of the Yakovlev Yak-40 - A. S. Kretov; V. V. Glukhov; D. V. Tinyakov (Научный вестник МГТУ ГА, 2024)
Nowadays Russia faces a big challenge of restoring the domestic passenger aircraft industry in the shortest possible time. This paper is devoted to the assessment of the potential to develop regional aircraft, which are of great importance not only for our country. The design and operational experience is an important link in the creation of any new aircraft. An extensive retrofit of the basic aircraft model is crucial in this process. The paper considers the conceptual assessment of the existing aircraft retrofit effectiveness, which is specifically related with the transition to composite wings, that provide a capability to increase the aspect ratio due to greater rigidity and reduce the aerodynamic drag, as a consequence. As a rule, the retrofit of out-of-date aircraft models necessarily involves the use of more advanced engines with enhancing performance, including better fuel efficiency. The study was conducted using the sensitivity analysis of takeoff weight to design changes, which has been well established for different types of aircraft. As a specific example, a draft version based on the Yak-40 regional jet is analyzed with a focus on the conducted experimental research carried out SIBNIA in 2012–2019. The results of extensive experimental research obtained by SIBNIA specialists are considered in this paper as a good basis for testing the performance and accuracy of the sensitivity analysis method. The obtained performance in the modified version of Yak-40 in terms of flight range comply well with the results of these practical studies. It is noted that the modified Yak-40 with a flight range of about 4000 km can be successfully operated not only as a regional, but also as a business jet. By its performance, the aircraft under consideration will not be inferior to known aircraft analogues. The paper emphasizes the relevancy to develop a new Russian engine for this aircraft category. In this respect, it is possible to consider a propulsion system with a thrust margin since the excess of internal volume of a passenger cabin can be used to increase the passenger capacity.